2013
DOI: 10.3390/d5040843
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Seed Quality of the “Badda” Common Bean from Sicily (Italy)

Abstract: The genetic structure of the “Badda” common bean cultivated at Polizzi Generosa, a village of Sicily (Palermo, Italy), was investigated using biochemical and molecular markers. Seed storage protein analysis by using SDS-PAGE, confirmed the attribution to the Andean gene pool. Simple Sequence Repeats (SSR) (or microsatellite) molecular markers provided useful information on genetic variation and relationships between “Badda bianco” and “Badda nero” morphotypes. Based on SSR data, the nine accessions examined we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…High-yielding combinations may also be identified by using either more-traditional crossbreeding methods [57,[69][70][71], or more-recently, molecular markers [41,72,73] or even near-infrared spectroscopy (NIRS) [74]. Molecular marker assisted breeding efforts of Raatz et al [75] characterised 708 bean varieties, landraces, and breeding lines using Single Nucleotide Polymorphism genotyping markers.…”
Section: Breeding For Increased Yield and Qualitymentioning
confidence: 99%
“…High-yielding combinations may also be identified by using either more-traditional crossbreeding methods [57,[69][70][71], or more-recently, molecular markers [41,72,73] or even near-infrared spectroscopy (NIRS) [74]. Molecular marker assisted breeding efforts of Raatz et al [75] characterised 708 bean varieties, landraces, and breeding lines using Single Nucleotide Polymorphism genotyping markers.…”
Section: Breeding For Increased Yield and Qualitymentioning
confidence: 99%
“…It was also concluded that seeds with Andean phaseolin type “C” (and “T”) are larger and oval, while seeds with Mesoamerican phaseolin type “S” are either square or kidney-shaped and medium to small in size [ 38 ]. As mentioned above, seeds of Andean origin are predominant in Europe, these seeds are medium to large in size and such types of the common bean are probably better adapted to environmental conditions and have been preferred by both farmers and consumers [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the centuries of its cultivation, this landrace has diverged into two easily distinguished morphotypes, i.e., "Badda bianco" (white badda) and "Badda nero" (black badda). The Badda morphotypes can be grouped into three distinct clusters, namely, Badda bianco accessions in one cluster and those of Badda nero in two separate, well-distinguished clusters [79].…”
Section: Assessing Diversity Among Heirloom Germplasmmentioning
confidence: 99%